An Exposition of God's Mission Based on Jonah 1 and its Implications for the Church's Mission Ministry - Laukapitang, Yunus; Walburg, Blake David; Camerling, Yosua Feliciano; Eunike, Sarah Citra (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2025)
The Ninevites worshipped Dagon. Therefore, God sent Jonah to Nineveh to show His love to the nation. This discussion focuses on understanding how God used Jonah’s disobedience to God’s call for the salvation of Nineveh and how important it is for the mission ministry of the church today. The trajectory of this paper follows the descriptive, investigative, and exegetical theological research genre. This paper is divided into three parts. The first part is an investigation of the exegetical aspects of Jonah 1. The second part is an exegetical exploration of the significance of God’s Mission in Jonah 1. The third part is the application of God’s mission based on Jonah 1 to the mission ministry of the church. This study finds that mission ministry is the work of God, obedience to God’s will, and mission ministry is cross-cultural. Based on Jonah 1, the involvement of God’s servants are basic tasks in conveying and spreading the gospel in the salvation work.